Kierkegaard's Literary Production by Quarterly Rates - Cappelørn, Niels J.; McKinnon, Alastair (Danske Studier, 2025)
Niels Jørgen Cappelørn and Alastair McKinnon on Kierkegaard's Literary Production by Quarterly Rates.